Single-nucleotide resolution detection of Topo IV cleavage activity in the Escherichia coli genome with Topo-Seq - Sutormin, Dmitry; Galivondzhyan, Alina; Gafurov, Azamat; Severinov, Konstantin (Frontiers in Microbiology, 2023)
Topoisomerase IV (Topo IV) is the main decatenation enzyme in Escherichia coli; it removes catenation links that are formed during DNA replication. Topo IV binding and cleavage sites were previously identified in the E. coli genome with ChIP-Seq and NorfIP. Here, we used a more sensitive, single-nucleotide resolution Topo-Seq procedure to identify Topo IV cleavage sites (TCSs) genome-wide. We detected thousands of TCSs scattered in the bacterial genome. The determined cleavage motif of Topo IV contained previously known cleavage determinants (−4G/+8C, −2A/+6 T, −1 T/+5A) and additional, not observed previously, positions −7C/+11G and −6C/+10G. TCSs were depleted in the Ter macrodomain except for two exceptionally strong non-canonical cleavage sites located in 33 and 38 bp from the XerC-box of the dif-site. Topo IV cleavage activity was increased in Left and Right macrodomains flanking the Ter macrodomain and was especially high in the 50–60 kb region containing the oriC origin of replication. Topo IV enrichment was also increased downstream of highly active transcription units, indicating that the enzyme is involved in relaxation of transcription-induced positive supercoiling.